The Intellectual Stress and Its Relationship with Personality' s Five Major Factors of Counselors (Journal Of Educational and Psychological Researches, 2014)
The current study aims at identifying:1-The intellectual stress of counselors according to gender variable (male, female ).2-The five major  factors of the  Counselor's  Personality.3-  The relationship between intellectual stress and the five major factors of the councilors' personality and according to gender variable (male, female ).4-The significant differences in the relationship between intellectual stress and the five major factors of the councilors' personality and according to gender variable  (male, female ).The sample of the study includes (260) counselors (130 male and 130 female ) taken from the General Directorates of Education in Baghdad during the academic year 2012-2013.The findings of the present study reveal that the counselors suffer from statistical significant intellectual stress and there is a correlation between intellectual stress and the five major factors of the councilors' personality. Moreover , the study reveals that the gender variable has an effect of the differences in the relationship between intellectual stress on one hand and the five major factors of personality on the second hand .